Antimicrobial activity of medicinal plants for their potential use in the Brazilian Unified Health System - Vanessa Feitosa Alves; Rebeca Dantas Figueiredo; Yuri Wanderley Cavalcanti; Wilton Wilney Nascimento Padilha (Revista Cubana de Estomatología, 2019)
Introduction: A list of 71 medicinal herbs has been published by the Brazilian Ministry of Health with the purpose of studying and developing medicines obtained from herbs for their potential use in the Unified Health System.